History! : the past as you've never seen it before. - DK Publishing, Inc.; Smithsonian Institution (New York, NY : DK Pub., 2019)
A visual history of the world that features explanations of events, illustrations, photographs, and computer-generated images.
The ancient world -- The medieval world -- The age of exploration -- The age of revolution -- The modern world.
Includes index.
Subtitle from front cover.
8.9
5-8.
5-8
Keywords: World history -- Juvenile literature; World history; World history